Question Number 114654 by mohammad17 last updated on 20/Sep/20

Commented bymohammad17 last updated on 20/Sep/20

help me sir

Commented bymohammad17 last updated on 20/Sep/20

thank hou sir can you help me in other question

Answered by bobhans last updated on 20/Sep/20

[2] x=acos^3  θ ⇒(dx/dθ) = −3acos ^2 θ sin θ          y=asin ^3 θ⇒(dy/dθ) = 3asin ^2 θ cos θ         (dy/dx) = (dy/dθ) × (dθ/dx) = ((3asin ^2 θ cos θ)/(−3acos ^2 θ sin θ))         (dy/dx) = −((sin θ)/(cos θ)) = −tan θ       (√(1+((dy/dx))^2 )) = (√(1+tan ^2 θ)) = sec θ

Answered by Dwaipayan Shikari last updated on 20/Sep/20

x^y =y^x   ylogx=xlogy  (y/x)+logx(dy/dx)=logy+(x/y).(dy/dx)  (dy/dx)(logx−(x/y))=logy−(y/x)  (dy/dx)=((logy−(y/x))/(logx−(x/y)))